2017
DOI: 10.5194/acp-17-7853-2017
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Paris NO<sub><i>x</i></sub> emissions from mobile MAX-DOAS observations and CHIMERE model simulations during the MEGAPOLI campaign using the closed integral method

Abstract: Abstract. We determined NOx emissions from Paris in summer 2009 and winter 2009/2010 by applying the closed integral method (CIM) to a large set of car multi-axis differential optical absorption spectroscopy (MAX-DOAS) measurements performed within the framework of the MEGAPOLI project (http://megapoli.dmi.dk/). MAX-DOAS measurements of the tropospheric NO2 vertical column density (VCD) were performed in large circles around Paris. From the combination of the observed NO2 VCDs with wind fields, the NO2 influx … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 20 publications
4
44
0
Order By: Relevance
“…1, with a coarse domain at a 15 km spatial resolution comprising most of Chile and a nested domain focusing on central Chile and centered on Santiago at a 3 km resolution. The meteorological conditions are simulated using the WRF model from the US National Center for Atmospheric Research (Skamarock et al, 2008). The model configuration used in this study to simulate and reproduce observed meteorological conditions is presented in Table 1.…”
Section: Model Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…1, with a coarse domain at a 15 km spatial resolution comprising most of Chile and a nested domain focusing on central Chile and centered on Santiago at a 3 km resolution. The meteorological conditions are simulated using the WRF model from the US National Center for Atmospheric Research (Skamarock et al, 2008). The model configuration used in this study to simulate and reproduce observed meteorological conditions is presented in Table 1.…”
Section: Model Setupmentioning
confidence: 99%
“…Mazzeo et al (2018) used a similar setup with a 2 km resolution for a sensitivity analysis of traffic and residential heating emissions in Santiago, yielding similar performances. Comparable CHIMERE simulations are performed for purposes of air quality operational forecast in France, whose performance at a small scale is acknowledged in the literature, provided emissions have appropriate magnitudes (Petit et al, 2017;Shaiganfar et al, 2017). Table 3.…”
Section: Simulation Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Vaughan et al (2016) and Karl et al (2017) reached similar conclusions by analyzing NO x flux measurements and attributed the discrepancy between observations and emission inventory estimates to the underrepresentation of the real-world road traffic emissions. Moreover, a general underestimation of the total NO x emissions, compared to TNO MEGAPOLI and MACC-III inventories, by a factor of 1.4-1.5 for the summer of 2009 in Paris was recently reported by Shaiganfar et al (2017), where they used a large set of car multi-axis differential optical absorption spectroscopy (MAX-DOAS) measurements to calculate the NO x emissions by applying the closed integral method (CIM). For the VOC emissions, there are reported emission uncertainties of ∼ 50 % for the anthropogenic sources (Theloke and Friedrich, 2007;Kuenen et al, 2014).…”
Section: Emissionsmentioning
confidence: 99%
“…The most common application is ground-based measurement (e.g., Irie et al, 2011;Pinardi et al, 2013;Wang et al, 2014;Chan et al, 2015;Xing et al, 2017). Meanwhile, mobile platform observations have been developed rapidly, e.g., carbased observations (Johansson et al, 2008;Shaiganfar et al, 2011Shaiganfar et al, , 2017Wang et al, 2012), aircraft observations (Baidar et al, 2013;Dix et al, 2016), and ship-based observations (Sinreich et al, 2010;Takashima et al, 2012;Peters et al, 2012;Schreier et al, 2015;Hong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%